(untitled) (Texas Journal of Engineering and Technology, 2025)
This article examines the criteria and indicators used to evaluate the effectiveness of digital transformation in energy enterprises. Emphasis is placed on both economic and technological aspects, as well as data management and service quality indicators. The study outlines a comprehensive framework based on theoretical approaches such as the neoclassical, institutional, and innovation-based views of effectiveness. A system of evaluation metrics—including ROI, NPV, automation levels, and consumer satisfaction—is presented, along with modern assessment methods such as the Balanced Scorecard (BSC), Analytic Hierarchy Process (AHP), and Data Envelopment Analysis (DEA). Practical applications are illustrated using statistical data from the digitalization initiatives of “National Electrical Networks of Uzbekistan” JSC. The results underscore the importance of integrated evaluation tools for effective strategic management in the context of energy sector digitalization